Design and operation of transfer lines for plasma wakefield accelerators using numerical optimizers - Ramjiawan, R; Doebert, S; Farmer, J; Gschwendtner, E; Velotti, FM; Verra, L; Della Porta, GZ; Bencini, V; Burrows, PN (American Physical Society, 2022)
The Advanced Wakefield (AWAKE) Experiment is a proof-of-principle experiment demonstrating the acceleration of electron beams via proton-driven plasma wakefield acceleration. AWAKE Run 2 aims to build on the results of Run 1 by achieving higher energies with an improved beam quality. As part of the upgrade to Run 2, the existing proton and electron beamlines will be adapted and a second plasma cell and new 150-MeV electron beamline will be added. The specification for this new 150-MeV beamline will be challenging as it will be required to inject electron bunches with micron-level beam size and stability into the second plasma cell while being subject to tight spatial constraints. In this paper, we describe the techniques used (e.g., numerical optimizers and genetic algorithms) to produce the design of this electron line. We present a comparison of the methods used in this paper with other optimization algorithms commonly used within accelerator physics. Operational techniques are also studied including steering and alignment methods utilizing numerical optimizers and beam measurement techniques employing neural networks. We compare the performance of algorithms for online optimization and beam-based alignment in terms of their efficiency and effectiveness.